Effects of hydrocolloid dressing in prevention of bed sore in patients undergoing coronary artery bypass surgery - Salsali M; Shaban M; Kamali P; NaderiPour A (Tehran University of Medical Sciences, 2004)
Introduction: Bed sore is an important complication of operation. Long immobility, hypotension and hypothermia in perioperative period predispose patients to bed sore. The prevention of bed sore is a priority in caring for immobilized patients and different methods have been used for this purpose. Hydrocolloid dressing is one of these methods. Materials and Methods: This study is a quasi-experimental research. Subjects consisted of 60 patients aged 40-70 years who had eligibility criteria for this study. Subjects were selected with convenience sampling and randomly allocated to two 30-patient groups (experimental and control). In experimental group, hydrocolloid dressing was used before surgery. No procedure was performed for control group. After surgery sacral area was examined on three occasions to detect bed sore: immediately, 24 and 48 hours after surgery. The data were collected by demographic questionnaire and staging bed sore checklist and analyzed by SPSS statistic program and use of descriptive methods such as Chi square, Fisher exact test, t test, ANOVA and least significant difference (LSD). Results: Incidence of bed sore was 13.3% in experimental group and %36.7 in control group. Chi square test showed significant difference between incidence of bed sore in two groups (p=0.03). Incidence of bed sore in two groups had no relationship with respect to gender and number of grafts. There was a significant relationship between bed sore and age, body mass index and duration of hypothermia, immobility and cardiopulmonary bypass (p<0.05). Conclusion: Considering findings of this research, it seems that use of hydrocolloid dressing is effective in preventing perioperative bed sore after coronary artery bypass surgery.